Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1743-0003-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Design and preliminary evaluation of the FINGER rehabilitation robot: controlling challenge and quantifying finger individuation during musical computer game play

Abstract: BackgroundThis paper describes the design and preliminary testing of FINGER (Finger Individuating Grasp Exercise Robot), a device for assisting in finger rehabilitation after neurologic injury. We developed FINGER to assist stroke patients in moving their fingers individually in a naturalistic curling motion while playing a game similar to Guitar Hero®a. The goal was to make FINGER capable of assisting with motions where precise timing is important.MethodsFINGER consists of a pair of stacked single degree-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 32 publications
(44 reference statements)
2
92
0
1
Order By: Relevance
“…We used the FINGER robotic exoskeleton 31,33 (Figure 1) to provide two levels of assistance to participants with stroke-related finger movement impairments while they played a musical computer game in the style of Guitar Hero. We randomized participants into high and low assistance groups and then dynamically adjusted the amount of robotic assistance each week to drive participants towards 85% and 50% success rates respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the FINGER robotic exoskeleton 31,33 (Figure 1) to provide two levels of assistance to participants with stroke-related finger movement impairments while they played a musical computer game in the style of Guitar Hero. We randomized participants into high and low assistance groups and then dynamically adjusted the amount of robotic assistance each week to drive participants towards 85% and 50% success rates respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Additional assurance that efforts would be comparable across groups comes from a pilot study in which we found that this task, game, and form of assistance caused participants to exert similar physical effort regardless of the assistance level (i.e. this system caused minimal slacking) 31 . Further, we quantified motivation and self-efficacy at multiple time points throughout training to better assess the psychological effects of assistance.…”
Section: Introductionmentioning
confidence: 94%
“…Several robots have been developed that assist movements of the hand isolated from the rest of the limb [10], [11], [12], [13], [14], [15], [16], [17], [18]. These devices require sitting in the clinic with the arm supported in a pre-defined posture and/or don’t allow interacting with objects.…”
Section: Introductionmentioning
confidence: 99%
“…The system, co-developed with Eric Wolbrecht of the University of Idaho in Moscow, helps users to move their fingers individually in a natural curling motion. The device captures their movements and monitors their effort and progress while they play a computer game similar to Guitar Hero, in which players use a guitar-shaped controller to simulate playing the real instrument 4 .…”
Section: Spring Into Actionmentioning
confidence: 99%